Effect of Chromolaena Odorata on Hepatotoxicology and Histopathology in the Liver Induced by Salmonella Typhi in Wistar Rats - Charles, Isirima Joshua; Minakiri, Siminialayi Iyeopu (European Scientific Journal, ESJ, 2018)
Typhoid fever, also known as enteric fever, is caused by the human restricted bacterial pathogen known as Salmonella enterica serovars typhi, which is always associated with liver pathology. This study attempts to investigate the Hepatotoxicological and Histopathological changes of the liver associated with Salmonella typhi infection in Wistar rats and to examine the potential of methanol leaf extract of Chromolaena odorata (MLECO) to reverse these adverse changes in comparison to ciprofloxacin treatment. The animals were divided into six groups: group 1 was normal control, group 2 was infected with Salmonella typhi without treatment (negative control), group 3, 4 and 5 were Salmonella typhi infected and treated with 100mg/kg, 200mg/kg and 400mg/kg of the extract respectively, and group 6 was infected and treated with 500mg/70kg of ciprofloxacin. The animals were inoculated with a single contagious dose of Salmonella typhi bacteria and were subsequently treated with the graded doses of the extract and 500mg/70kg dose of ciprofloxacin for a period of fifteen days, after the animals were confirmed infected. The rats were humanely sacrificed using diethyl ether anesthesia and blood samples taken for liver function investigation and liver harvested and processed for histological examination. MLECO reversed the adverse hepatotoxicological and pathological changes in the liver induced by S. tyhi infection in a dose-dependent manner. This was done with the 200mg and 400mg doses being more effective at reversing liver changes than ciprofloxacin.